How to identify peer-reviewed publications: Open-identity labels in scholarly book publishing - Kulczycki, Emanuel; Rozkosz, Ewa A.; Engels, Tim C. E.; Guns, Raf; Hołowiecki, Marek; Pölönen, Janne (My University, 2019)
This article discusses the open-identity label, i.e., the practice of disclosing reviewers’ names in published scholarly books, a common practice in Central and Eastern European countries. This study’s objective is to verify whether the open-identity label is a type of peer-review label (like those used in Finland and Flanders, i.e., the Flemish part of Belgium), and as such, whether it can be used as a delineation criterion in various systems used to evaluate scholarly publications. We have conducted a two-phase sequential explanatory study. In the first phase, interviews with 20 of the 40 largest Polish publishers of scholarly books were conducted to investigate how Polish publishers control peer reviews and whether the open-identity label can be used to identify peer-reviewed books. In the other phase, two questionnaires were used to analyze perceptions of peer-review and open-identity labelling among authors (n = 600) and reviewers (n = 875) of books published by these 20 publishers. Integrated results allowed us to verify publishers’ claims concerning their peer-review practices. Our findings reveal that publishers actually control peer reviews by providing assessment criteria to reviewers and sending reviews to authors. Publishers rarely ask for permission to disclose reviewers’ names, but it is obvious to reviewers that this practice of disclosing names is part of peer reviewing. This study also shows that only the names of reviewers who accepted manuscripts for publication are disclosed. Thus, most importantly, our analysis shows that the open-identity label that Polish publishers use is a type of peer-review label like those used in Flanders and Finland, and as such, it can be used to identify peer-reviewed scholarly books.
This work was supported by the Ministry of Science and Higher Education in Poland (https://www.gov.pl/nauka/) within the DIALOG Programme: the project title ‘Research into Excellence Patterns in Science and Art’. Tim Engels and Raf Guns thank the Flemish government for its funding of the Center for R&D Monitoring (ECOOM). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.
Keywords: scholarly books; peer-review; open-identity label; peer-review label